RETRACTED ARTICLE: Flawless polyaniline coating for preservation and corrosion protection of ancient steel spearheads: an archaeological study from military museum, Al-Qala, Egypt - Mohamed M. Megahed; Noha H. Elashery; Saleh M. Saleh; Ashraf M. El-Shamy (Scientific Reports, 2024)
Abstract The purpose of this research was to examine the viability of applying a flawless polyaniline coating on steel spearheads to preserve them and protect them from corrosion. The spearpoints, thought to be archaeologically significant, were acquired from the Military Museum in Al-Qala, Egypt. X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy were used to characterize the spearheads chemical composition and microstructure (EDX). The spearheads were determined to be constructed of steel and to have a coating of ferric oxide and other corrosion products on their exteriors. After that, a flawless polyaniline coating was electrochemically deposited onto the spearpoints in a way that was both quick and cheap. Many types of corrosion tests, such as electrochemical impedance spectroscopy and potentiodynamic polarization (PDP) readings, were used to determine the coating’s effectiveness. The steel spearheads’ findings revealed a significant improvement in their resistance to corrosion after being coated with flawless polyaniline. The coating served as a barrier, blocking out water and other corrosive substances and slowing the buildup of corrosion byproducts on the spearpoints. In conclusion, our research shows that a flawless polyaniline coating may be an effective anti-corrosion treatment for ancient steel artifacts. The approach is straightforward, cheap, and readily scalable for massive conservation efforts.